Assessment of groundwater quality and its suitability for drinking in the ouargla region northeastern Algerian Sahara - Abdelmalek Merkhoufi; Samir Kateb; Kais Baouia; Samir Djireb (International Journal of Computational and Experimental Science and Engineering, 2026)
This study focused on the determination of the different physicochemical characteristics of groundwater from 59 boreholes distributed over the three main aquifers of the Ouargla region (South-East of Algeria). The quality of the water was also assessed in order to evaluate their amenities and the international standards of drinking water quality of the World Health Organization (WHO) and the water quality index (WQI). The physicochemical parameters selected for this study, namely pH, total dissolved solids, electrical conductivity, total hardness, alkalinity, calcium, magnesium, sodium, potassium, bicarbonate, chloride, sulfate, and Temperature, were determined by following the procedures prescribed by international standards. were determined by following the procedures prescribed by international standards. In groundwater quality studies, statistical analysis techniques such as correlation analysis, principal component analysis (PCA) and analysis of variance (ANOVA) were used to assess the main factors and mechanisms governing spatial variations in the Ouargla basin region. The results obtained showed that the facies characterizing the study area were a mixed combination of Ca–Mg–Cl, Ca-Cl and Na-Cl, with the dominant ions being most often chlorides and sulfates, as well as calcium and magnesium. The WQI values ​​calculated for the Ouargla basin region ranged from 174.69 to 312.71. The geospatial distribution of the water quality index shows that the water of the Albian aquifer is poor, while the majority of the water of the Miopliocene and Senonian aquifers is very poor. However, the results of this study indicate that most of the water is not potable and requires additional pre-treatment before consumption.